Just what the nurse practitioner ordered: Independent prescriptive authority and population mental health - Diane Alexander; Molly Schnell (Federal Reserve Bank of Chicago, 2017)
We examine whether relaxing occupational licensing to allow nurse practitioners (NPs) - registered nurses with advanced degrees - to prescribe medication without physician oversight is associated with improved population mental health. Exploiting time-series variation in independent prescriptive authority for NPs from 1990 - 2014, we find that broadening prescriptive authority is associated with improvements in self-reported mental health and decreases in mental-health-related mortality, including suicides. These improvements are concentrated in areas underserved by psychiatrists and among populations traditionally underserved by mental health providers. Our results demonstrate that extending prescriptive authority to NPs can help mitigate physician shortages and extend care to disadvantaged populations.
Keywords: 330